GAMBARAN PENERAPAN TELEHEALTH DALAM PENCEGAHAN TEXT NECK SYNDROME SELAMA ONLINE CLASS STT TRI KAYA SUDHA PARAMARTHA - Paramurthi, I.A. Pascha; Pramesti, Luh Dian Raika; Novianti, I Gusti Ayu Sri Wahyuni (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
COVID-19 has an impact on the education sector. Learning takes place online and students wear gadgets for a long time. This causes posture disorders, especially the neck area known as text neck syndrome (TNS). The purpose of the study is to find out an overview of the application of telehealth in the prevention of TNS. This type of research is quantitative with observational research design. Research respondents obtained using purposive sampling techniques obtained by 20 Sekaa Teruna Teruni Tri Kaya Sudha Paramartha Banjar Adat Pande, Bangli. The research was conducted on September 17, 2021. Post test results after implementation of telehealth in the form of video, digital posters and zoom media consultations there was an increase in knowledge as many as 20 respondents (100%) understand TNS prevention and as many as 18 respondents (90%) understand the exercises for TNS. This occurred an increase in respondents’ knowledge about the negative effects of gadgets with a long duration and TNS. Related to complaints of neck pain after TNS prevention education 2 respondents (20%) who complained of neck pain after the implementation of telehealth. STT is able to understand negative effects such as TNS that can occur due to the use of gadgets with a long duration and understand exercises that can be done to prevent the occurrence of TNS. Respondents received information after participating in socialization in daily activities with a perceived effect, the average STT member has no pain after applying the information obtained. Respondents 100% said they had educated the closest people or people around them about TNS. COVID-19 memberikan dampak pada sektor pendidikan. Pembelajaran berlangsung online dan siswa memakai gadget dalam waktu yang lama. Ini menimbulkan gangguan postur tubuh terutama area leher yang dikenal dengan text neck syndrome (TNS). Tujuan penelitian untuk mengetahui gambaran penerapan telehealth dalam pencegahan TNS. Jenis penelitian ini kuantitatif dengan desain penelitian observasi. Responden penelitian diperoleh menggunakan teknik purposive sampling didapatkan 20 Sekaa Teruna Teruni Tri Kaya Sudha Paramartha Banjar Adat Pande, Bangli. Penelitian dilaksanakan pada 17 September 2021. Hasil post test setelah penerapan telehealth berupa video, poster digital dan konsultasi media zoom terjadi peningkatan pengetahuan sebanyak 20 responden (100%) memahami pencegahan TNS dan sebanyak 18 responden (90%) memahami latihan untuk TNS. Hal ini terjadi peningkatan pengetahuan responden mengenai efek negatif gadget dengan durasi yang lama dan TNS. Terkait keluhan nyeri leher setelah edukasi pencegahan TNS 2 responden (20%) yang mengeluhkan nyeri leher setelah penerapan telehealth. STT memahami efek negatif seperti TNS yang dapat terjadi akibat penggunaan gadget dengan durasi lama dan memahami exercise yang dilakukan untuk mencegah terjadinya TNS. Responden menerapakan informasi setelah mengikuti sosialisasi dalam kegiatan sehari-hari dengan efek yang dirasakan, yaitu rata-rata anggota STT sudah tidak mengalami nyeri setelah menerapkan informasi yang didapat. Responden sebanyak 100% menyatakan sudah mengedukasi orang-orang terdekat atau orang yang berada disekitar mereka mengenai TNS.